Narrative research and audiodescription: Another methodological option - Silva, Manoela Cristina Correia Carvalho da (2022)
Narrative research is a methodology that consists in collecting stories about a particular subject in search of information to understand a specific phenomenon. In general, it is used as a resource to give voice to the subjects of a study. In this article, we present an example of how narrative research can be used as an alternative to traditional reception studies in the area of audio description (AD). To do so, we look at the methodological path of the doctoral thesis entitled Para além do visível: princípios para uma audiodescrição menos visocêntrica, in which two autobiographies by people with acquired blindness were analyzed: Touching the Rock, by John Hull, and Out of Darkness: A Memoir, by Zoltan Torey. The works were studied through the use of narrative research methodology, and thematic analysis as devised by Braun and Clarke. The analysis undertaken emphasized the importance of elements such as respect for the different profiles of the target audience, the inclusion of early and continued high-quality exposure, and the association of AD with multisensory experiences.